Ascorbic acid prevents yellowing of fresh-cut yam by regulating pigment biosynthesis and energy metabolism. (July 2022) - Zhao, Xiaoyan; Guo, Shuang; Ma, Yue; Zhao, Wenting; Wang, Pan; Zhao, Shuang; Wang, Dan
Graphical abstract: Highlights: Dipping fresh-cut yams in 2% ascorbic acid represses yellowing during storage. TCA cycle activity, and thus energy metabolism, are decreased by ascorbic acid. Ascorbic acid inhibits carotenoid, flavonoid and bisdemethoxycurcumin biosynthesis. Abstract: The fresh-cut yam would turn yellow under 25 ℃ for 36 h, which could reduce consumer's acceptance. This study aimed to investigate the mechanism by which 2% ascorbic acid inhibits yellowing of fresh-cut yam by detecting enzyme activities, gene expressions and metabolites. Ascorbic acid treatment was found to decrease ATPase activities, ATP content, and energy charge. The transcriptional expression levels of citrate synthase, acetyl-CoA carboxylase, and acetyl-CoA synthetase, which are involved in the tricarboxylic acid cycle, were also decreased by ascorbic acid treatment, thus blocking the supply of precursors and energy for pigment biosynthesis. In addition, ascorbic acid effectively inhibited the formation of carotenoids, flavonoids, and bisdemethoxycurcumin, as indicated by lower metabolic levels, decreased enzyme activities, and downregulated transcriptional expressions. Thus, ascorbic acid prevents yellowing in fresh-cut yam by reducing the energy metabolism level as well as inhibiting pigment (carotenoids, flavonoids, bisdemethoxycurcumin) biosynthesis pathways. Accordingly, ascorbic acid treatment is a safe, effective, and cheap method for inhibiting fresh-cut yam yellowing.